Analisis Risiko Pengawasan Terhadap Meningkatnya Peredaran Barang Dan/Atau Jasa Yang Tidak Sesuai Ketentuan - Bairam, Vander Wilden; Grace, Maggie (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
The purpose of this study is to provide an overview of handling high risk by mitigating the risk of unwanted events (KTD) against objectives at the Directorate of Control of Circulating Goods and Services of the Ministry of Trade on Key Performance Indicators from Organizations. The type of research used is quantitative where the research disseminates questions on the large, medium, and small impact scales of a risk statement and the data collection technique is through observation, as well as in-depth interviews of emerging risk statements. The results of the research show that through bowtie analysis the impact and the chance of a risk occurring can be reduced by mitigating and approaching large and medium-scale risks into a small and missing risk scale. Out of 3 (three) risk statements, 2 (two) risk statements can be reduced and 1 missing risk statement after the mitigation is carried out, namely the unsupervised circulation of goods and services in areas that are not reached by the Mitigation Supervisory Officer, the additional human resources for the Goods and Services Supervisor Officer through Education and Training are carried out.